Класифікація юридичних конструкцій як засобів законотворчої техніки - Дутко, А. О. (Видавництво Львівської політехніки, 2014)
Аналізується класифікація юридичних конструкцій, подана різними авторами. Виділяються види юридичних конструкцій як засобів законотворчої техніки за сферою застосування, за видами галузей позитивного права, за функціями галузей у правовому регулюванні, за складом, за способом закріплення, за поділом системи права на публічне та приватне тощо. Анализируется классификация юридических конструкций, представлена различными авторами. Выделяются виды юридических конструкций как средств законотворческой техники по сфере применения, по видам отраслей позитивного права, по функциям отраслей в правовом регулировании, по составу, по способу закрепления, за разделением системы права на публичное и частное т. п. Analyzes the classification of legal constructions, presented by various authors. Select the types of legal constructions as a means of legislative technique for field use (common law, intersectoral and sectoral), by type of branches of positive law (constitutional, administrative law, civil law, criminal law, etc.), by dividing the legal system for public and private (public law and private law), by functions in the areas of legal regulation (material and procedural), by composition (simple and complex), in the formof laws, which are fixed structures (codification, the construction the current legislative), the method of fixing (textual and semantic).
Классификация юридических конструкций как средств законотворческой техники
Classification of legal constructions as means of lawmaking technique
Keywords: законотворча техніка; засіб законотворчої техніки; юридична конструкція; види юридичних конструкцій; законотворческая техника; средство законотворческой техники; юридическая конструкция; виды юридических конструкций; legal constructure; legislative technique; means of legislative technique; types of legal constructures